Sustained Release of Voriconazole Using 3D-Crosslinked Hydrogel Rings and Rods for Use in Corneal Drug Delivery - Aiym Rakhmetova; Zhiqi Yi; Malake Sarmout; Leo H. Koole (Gels, 2023)
Corneal disorders and diseases are prevalent in the field of clinical ophthalmology. Fungal keratitis, one of the major factors leading to visual impairment and blindness worldwide, presents significant challenges for traditional topical eye drop treatments. The objective of this study was to create biocompatible 3D-crosslinked hydrogels for drug delivery to the cornea, intending to enhance the bioavailability of ophthalmic drugs. Firstly, a series of flexible and porous hydrogels were synthesized (free-radical polymerization), characterized, and evaluated. The materials were prepared by the free-radical polymerization reaction of 1-vinyl-2-pyrrolidinone (also known as N-vinylpyrrolidone or NVP) and 1,6-hexanediol dimethacrylate (crosslinker) in the presence of polyethylene glycol 1000 (PEG-1000) as the porogen. After the physicochemical characterization of these materials, the chosen hydrogel demonstrated outstanding cytocompatibility in vitro. Subsequently, the selected porous hydrogels could be loaded with voriconazole, an antifungal medication. The procedure was adapted to realize a loading of 175 mg voriconazole per ring, which slightly exceeds the amount of voriconazole that is instilled into the eye via drop therapy (a single eye drop corresponds with approximately 100 mg voriconazole). The voriconazole-loaded rings exhibited a stable zero-order release pattern over the first two hours, which points to a significantly improved bioavailability of the drug. Ex vivo experiments using the established porcine eye model provided confirmation of a 10-fold increase in drug penetration into the cornea (after 2 h of application of the hydrogel ring, 35.8 ± 3.2% of the original dose is retrieved from the cornea, which compares with 3.9 ± 1% of the original dose in the case of eye drop therapy). These innovative hydrogel rods and rings show great potential for improving the bioavailability of ophthalmic drugs, which could potentially lead to reduced hospitalization durations and treatment expenses.